A Study to Analyze the Tentorial Incisura in Indian Population, for Racial Differences and Its Impact in the Outcome of Patients with Head Injury - Kunjithapatham, Deiveegan; Pachiyappan, Jeyaselvasenthilkumar Thotalampatti; Fernand, Maria Subison Soosai (Indian Journal of Neurosurgery, 2018)
Aim To measure the size of tentorial notch in Indian population, compare it with the western population from the literature available, and analyze the relation between size of tentorial notch and the outcome in patients with head injury.Materials and Methods The study was done using 10 cadavers and 15 autopsy specimens. In all the specimens, tentorial incisura was measured using vernier caliper after opening the skull and cutting the midbrain at the level of tentorial edge carefully without damaging the tentorium. All measurements were done in millimeters.Results Mean values, age-dependent mean values, and percentile values were calculated for various parameters in the tentorial incisura. Majority of the tentorial incisura are of typical type. Cases of tentorial incisura are significantly smaller in the age group of 20 to 25 years. Rate of deterioration of Glasgow coma scale (GCS) is rapid when the tentorial incisura is large.Conclusion There were no significant variations in measurements of tentorial incisura in Indian population compared with the western population. Rate of deterioration of GCS is higher in patients who had large tentorial incisura compared with other groups, which is statistically significance. However, this is to be confirmed by further study using large groups of patients to be used for clinical applications.
Keywords: tentorial incisura; tentorial herniation; tentorial notch